2021
DOI: 10.1007/s10811-020-02357-0
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining spores for the production of Saccharina latissima: seasonal limitations in nature, and induction of sporogenesis in darkness

Abstract: When cultivating the kelp Saccharina latissima, knowledge on the availability of seeding material for the production is essential. Applying a spore seeding approach requires spores from the reproductive organs of the fertile sporophytes (sori). As sori are generally not present during the time of seeding in late summer, the production of spores (sporogenesis) can be artificially induced by removing the meristematic part of the sporophyte and keeping the sporophyte under short day, temperate, and nutrient-reple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Kelp species are widespread in temperate regions, which are characterised by strong seasonal variation in daylength, light intensity and temperature (Lüning 1993). In general, growth and reproduction of kelps show clear seasonal patterns (Kain 1979;Novaczek 1984a; Lee and Brinkhuis 1988;Fairhead and Cheshire 2004;Bartsch et al 2008;Miller et al 2012;Boderskov et al 2021) and the reproduction of sporophytes (formation of sorus) is driven by short daylengths (Lüning 1988;Pang and Lüning 2004;Boderskov et al 2021) and occurs during periods of low or no growth (Kain 1979). Similarly, daylength is the trigger for the reproduction of gametophytes in kelps, although the requirements for the formation of antheridia and oogonia (gametogenesis) are species-specific (Choi et al 2005;Nelson 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Kelp species are widespread in temperate regions, which are characterised by strong seasonal variation in daylength, light intensity and temperature (Lüning 1993). In general, growth and reproduction of kelps show clear seasonal patterns (Kain 1979;Novaczek 1984a; Lee and Brinkhuis 1988;Fairhead and Cheshire 2004;Bartsch et al 2008;Miller et al 2012;Boderskov et al 2021) and the reproduction of sporophytes (formation of sorus) is driven by short daylengths (Lüning 1988;Pang and Lüning 2004;Boderskov et al 2021) and occurs during periods of low or no growth (Kain 1979). Similarly, daylength is the trigger for the reproduction of gametophytes in kelps, although the requirements for the formation of antheridia and oogonia (gametogenesis) are species-specific (Choi et al 2005;Nelson 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For all seeding events, a minimum of 10 sporophytes was used for spore extraction. The sporophytes were collected during May -July 2018 and 2019, and artificially induced to produce spores in darkness in an intermediate bulk container (IBC) of 1000 L with up to 50 sporophytes per tank, according to Boderskov et al (2021b). The spores were released from fertile tissue, and counted in a Thoma hemocytometer counting chamber prior to seeding.…”
Section: Seeding Of Cultivation Lines and Netsmentioning
confidence: 99%
“…Sporogenesis in S. latissima can also be induced efficiently out of season in total darkness (Boderskov et al 2021).…”
Section: Cultivation Strategies -Nurserymentioning
confidence: 99%
“…The seeding methods did not affect the biomass's protein content when harvested. A Danish study compared biomass yield and quality between direct seeding and traditional spore seeding on twine and two substrates, including three deployment times at three different cultivation sites (Boderskov et al 2021). The main findings showed that the direct seeding method gave yields comparable to the traditional seeding method with spores at the most exposed site, whereas at the sheltered sites, the highest biomass yield was achieved using the traditional spore seeding method.…”
Section: Cultivation Strategies -Nurserymentioning
confidence: 99%